Correlates of HIV infection and being unaware of HIV status among soon-to-be-released Ukrainian prisoners. - Azbel, Lyuba; Wickersham, Jeffrey A; Grishaev, Yevgeny; Dvoryak, Sergey; Altice, Frederick L (Journal of the International AIDS Society, 2014)
Prisoners bear a disproportionate burden of Ukraine's volatile and transitional HIV epidemic, yet little is known in Eastern Europe about HIV testing, treatment and HIV-related risk among prisoners.
Keywords: Adolescent; Adult; Aged; Cross-Sectional Studies; Female; HIV Infections; Humans; Male; Middle Aged; Prisoners; Risk Factors; Ukraine; Young Adult